Digital Content Optimization for Personal Branding and Increasing Digital Literacy for Students of MA Miftahul Ulum Puntir Purwosari Pasuruan: Optimalisasi Konten Digital Untuk Personal Branding dan Peningkatan Literasi Digital Bagi Siswa MA Miftahul Ulum Puntir Purwosari Pasuruan - Rosadi, Muhammad Imron; Siti Muyasaroh; Zainul Ahwan; Ninuk Riswandari; Ahmad Aminuddin; Riska Amelia (Jurnal Soeropati, 2023)
This program is intended to increase the capacity of knowledge, understanding and ability to improve personal branding through digital content as well as digital literacy for MA Miftahul Ulum Puntir Purwosari Pasuruan students in utilizing information and communication technology, namely smartphones and social media in a positive and maximum way. The results of the service show that students' understanding of personal branding and digital literacy is still relatively low, this can be seen based on questions and answers with training participants. Furthermore, comprehensive training related to optimizing personal branding through digital contexts and understanding related to digital literacy was given by a community service team who are members of the Pasuruan ICT volunteer community, informatics study program and communication science study program Yudharta University of Pasuruan. The results of this training show significant changes related to understanding and increasing digital content processing capabilities for personal branding and digital literacy through interviews and testimonials to participants.